Free space optical communication with spatial diversity based on orbital angular momentum of light - Raoof Mehrpoor, Gilda; Safari, Majid; Schmauß, Bernhard (Optical Wireless Communications (IWOW), 2015 4th International Workshop on, 2015)
In this paper, the use of optical beams carrying orbital angular momentum (OAM) is proposed to provide spatial diversity gains for free space optical communication links degraded by atmospheric turbulence. We show that transmitted beams carrying sufficiently separated OAM modes experience highly uncorrelated turbulence effects. Furthermore, the outage probability analysis confirms that spatial diversity gain is achievable using the proposed technique without requiring the deployment of multiple apertures which is necessary for traditional spatial diversity scheme
lhft_intern.bib::mehrpoor2015free